Time-efficient sintering processes to attach power devices using nanosilver dry film - Dai, Jingru; Li, Jianfeng; Agyakwa, Pearl; Johnson, Christopher Mark (iMAPSource, 2017)
Pressure-assisted sintering processes to attach power devices using wet nanosilver pastes with time scales of minutes to a few hours have been widely reported. This paper presents our work on time-efficient sintering, using nanosilver dry film and an automatic die pick and place machine, resulting in process times of just a few seconds. The combined parameters of sintering temperature 250 °C, sintering pressure 10 MPa and sintering time 5 s were selected as the benchmark process to attach 2 mm × 2 mm × 0.5 mm dummy Si devices. Then the effects of either the sintering temperature (240 to 300 °C), time (1 to 9 s) or pressure (6 to 25 MPa) on the porosity and shear strength of the sintered joints were investigated with 3 groups and a total of 13 experimental trials. The average porosities of 24.6 to 46.2% and shear strengths of 26.1 to 47.7 MPa are comparable with and/or even better than those reported for sintered joints using wet nanosilver pastes. Their dependences on the sintering temperature, time and pressure are further fitted to equations similar to those describing the kinetics of sintering processes of powder compacts. The equations obtained can be used to not only reveal different mechanisms dominating the densification and bonding strength, but also anticipate the thermal-induced evolutions of microstructures of these rapidly sintered joints during future reliability tests and/or in service.